Financial Development and Survival of African Agri-food Exports - Jaud, Melise; Kukenova, Madina (2012)
This paper investigates the link between export survival of agri-food products and financial development. It tests the hypothesis that financial development differentially affects the survival of exports across products based on their need of external finance. The authors test whether exports of products that are relatively more reliant on external capital survive longer when initiated in more financially developed countries. The results suggest that agri-food products that require more external finance indeed sustain longer in foreign markets if the exporting country is more financially developed.